2002
DOI: 10.1046/j.1523-1755.2002.00213.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aggressive blood pressure control in normotensive type 2 diabetic patients on albuminuria, retinopathy and strokes

Abstract: Over a five-year follow-up period, intensive (approximately 128/75 mm Hg) BP control in normotensive type 2 diabetic patients: (1) slowed the progression to incipient and overt diabetic nephropathy; (2) decreased the progression of diabetic retinopathy; and (3) diminished the incidence of stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
459
0
32

Year Published

2003
2003
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 748 publications
(497 citation statements)
references
References 35 publications
5
459
0
32
Order By: Relevance
“…9 Even in normotensive diabetic patients, lowering blood pressure can be beneficial in controlling diabetic nephropathy and retinopathy. 10 In particular, in patients with type 2 DM, the risk of diabetic nephropathy and retinopathy was independently and additively attributable to hypertension and hyperglycemia. 6 Arterial hypertension is a main risk factor in the development and progression of diabetic nephropathy, 9 and a sustained reduction in blood pressure is probably the most effective single intervention to slow the progression of nephropathy in type 1 and type 2 DM.…”
Section: Clinical and Epidemiological Evidence Of The Detrimental Effmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Even in normotensive diabetic patients, lowering blood pressure can be beneficial in controlling diabetic nephropathy and retinopathy. 10 In particular, in patients with type 2 DM, the risk of diabetic nephropathy and retinopathy was independently and additively attributable to hypertension and hyperglycemia. 6 Arterial hypertension is a main risk factor in the development and progression of diabetic nephropathy, 9 and a sustained reduction in blood pressure is probably the most effective single intervention to slow the progression of nephropathy in type 1 and type 2 DM.…”
Section: Clinical and Epidemiological Evidence Of The Detrimental Effmentioning
confidence: 99%
“…6 Arterial hypertension is a main risk factor in the development and progression of diabetic nephropathy, 9 and a sustained reduction in blood pressure is probably the most effective single intervention to slow the progression of nephropathy in type 1 and type 2 DM. 7,[9][10][11] In the Wisconsin Epidemiology Study of DR, the presence of hypertension in type 1 diabetic patients was associated with a 73% increase in the risk of incident proliferative DR. 12 More recently, the Wisconsin Epidemiology Study of DR demonstrated that the 25-year incidence of visual impairment was related to poorer glycemia control and the presence of arterial hypertension. In these patients, the presence of arterial hypertension increases the risk of visual impairment by 72%.…”
Section: Clinical and Epidemiological Evidence Of The Detrimental Effmentioning
confidence: 99%
“…34,40,[46][47][48][56][57][58][59] Clinical trials, grouped by the degree of albuminuria, demonstrating the beneficial effects of RAAS inhibition on renal end points in patients with diabetes mellitus are summarized in Table 2. 34,40,42,48,49,[57][58][59][60][61][62][63][64][65][66][67][68][69][70][71] Normoalbuminuria The Bergamo Nephrologic Diabetes Complications Trial (BENEDICT) is the only primary prevention study to date to demonstrate that the development of microalbuminuria can be prevented by the use of an ACE inhibitor alone or in combination with a CCB in hypertensive normoalbuminuric patients with type II diabetes. 59 …”
Section: Clinical Evidence Of Benefits Of Raas Inhibition In Patientsmentioning
confidence: 99%
“…In type II diabetes, several studies have demonstrated that ARBs and ACE inhibitors can reduce the progression of microalbuminuria, and some of these trials will be discussed in more detail later in this article. 40,58,63 Macroalbuminuria In patients with type I diabetes and proteinuria, captopril reduced the risk of progression of nephropathy by 48% vs placebo; the risk reduction was greater in patients with higher baseline serum creatinine levels. 48 Captopril also halved the risk of the combined end point of death, dialysis, or transplantation in these patients.…”
Section: Microalbuminuriamentioning
confidence: 99%
“…Normotensive patients with advanced DN show slower progression compared with hypertensive patients. [33][34][35][36][37][38][39][40][41][42] Non-pharmacologic approaches (dietary modifications especially and increased physical activity) are effective in reducing BP in non-diabetic individuals 43 and may have similar benefits for diabetic patients. However, pharmacologic approaches remain the mainstay for controlling BP in patients with DM.…”
Section: Blood Pressure Controlmentioning
confidence: 99%